First- and Second-Order Methodological Developments from the Coleman Report - Samuel R. Lucas (RSF: The Russell Sage Foundation Journal of the Social Sciences, 2016)
Equality of Educational Opportunity was a watershed for sociological engagement with public policy, yet the questions the project addressed drew attention to several challenging methodological issues. Statistical advances, such as the multilevel model, were important first-order developments from the Coleman Report. Second-order developments, however, may be far less visible but perhaps even more important. Second-order developments of the Coleman Report stem from two sources: (1) social scientists’ reactions to proposed resolutions of the statistical challenges that the report navigated, and (2) Coleman’s own (perhaps implicit) theoretical response to criticisms of such works as Equality of Educational Opportunity. Heightened interest in the challenge of identification serves as an example of the former type of second-order effect, whereas “Coleman’s boat” (Coleman 1990)—and the social analytics that adopt, among other approaches, simulation strategies of inquiry consistent with Coleman’s typology of causal pathways—serves as an example of the latter. First-order developments take the questions as given and see the challenge as a practical, technical issue; second-order developments explicitly or implicitly reassess the question, treating the challenge as epistemological or social-theoretic. Second-order developments therefore may change the game, upsetting or rejecting routine practice at a fundamental level. I contend that as knowledge of second-order developments and their means of practical implementation in analyses diffuses among social analysts, they will prove of far more value than first-order developments to social understanding, sociology, and social policy.